Educational Technology and Innovation in Islamic Education Planning - Oktoberi, Rezki; Fikri, Muhammad Sodiqul; Romlah, Romlah; Abdurrahman, Abdurrahman (Journal Corner of Education, Linguistics, and Literature, 2025)
The purpose of this research was to analyze the application of educational technology and innovation in Islamic education planning in the digital era. This study used literature research methods and qualitative descriptive approaches to explore various literature related to the concept of educational technology, curriculum innovation, collaborative learning models, planning of technology-based facilities and infrastructure. The findings of the study show that the use of technologies such as blended learning, immersive learning (VR/AR), and the integration of digital literacy into the Islamic education curriculum can increase the effectiveness, interactivity, and relevance of learning to the needs of the 21st century. In addition, innovation in human resource development and education budget management is the key to further application of technology in Islamic educational institutions. By integrating Islamic values and technological advancements, the Islamic education system can transform to be more adaptive, innovative and competitive in facing the challenges of the digital era.